CRIMINAL RESPONSIBILITY FOR PHISHING AND CARDING OFFENDERS UNDER ITE LAW AND CRIMINAL CODE - Enna Budiman; Timbo Mangaranap Sirait (JILPR Journal Indonesia Law and Policy Review, 2026)
The development of information technology in the era of the Industrial Revolution 4.0 is like a double-edged sword: while it brings positive impacts, it also gives rise to various forms of cybercrime, such as phishing and carding, which require law enforcement measures through the imposition of criminal liability on the offenders. This research applies a normative juridical method through library-based legal research. The findings conclude as follows: First, although Indonesian laws provide a clear legal basis for addressing information and electronic transaction (ITE) crimes, particularly phishing and carding, law enforcement implementation remains superficial and highly dependent on the capacity of law enforcement officers, with a tendency to focus only on apprehended offenders without further tracing the supporting actors behind them. Second, the effectiveness of the existing legal framework in handling ITE crimes committed by individuals who are exploited by cybercrime organizations has not been optimal, as international cooperation mechanisms have not been effective. Third, the concepts of criminal liability and sentencing applied in judicial decisions regarding phishing and carding cases are normatively appropriate; however, substantively, the sentencing in these decisions has not fully reflected the concept of criminal liability, which requires a broader assessment of the offender’s conduct. As a result, criminal responsibility and sentencing become disproportionate.